1994
DOI: 10.1007/bf00121159
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniformity of sarcomere lengths can explain the ?catch-like? effect of arthropod muscle

Abstract: The 'catch-like' effect, a hysteresis phenomenon in arthropod skeletal muscle contraction thought to be related to the catch of molluscan smooth muscle, was investigated in the closer muscle of the crab Eriphia spinifrons. Several parameters were varied to determine their influence on the catch-like effect. These parameters were (1) the frequency of repetitive stimulation of the slow excitatory neuron, (2) additional stimulation of the inhibitory neuron, (3) the amount of stretch applied to the muscle and (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is well-known that crustaceans are able to generate higher maximum muscle stresses than vertebrates and most insects ( Josephson 1993). However, the physiological basis of this di¡erence has remained unresolved: are the higher stresses due simply to increases in the resting sarcomere length or is it necessary to invoke other ¢breassociated traits such as the density of the myosin ¢laments ( Jahromi & Atwood 1969;West et al 1992), arthropod`catch-like' e¡ects (GÏnzel & Rathmayer 1994), the myo¢brillar bundle diameter (Hilber & Galler 1998), di¡erences in the actin^myosin ¢lament ratios ( Jahromi & Atwood 1969;West et al 1992) and potential di¡erences in the actin^myosin cross-bridge duty factors (Cooke 1997)? Because of the heterogeneous nature of crustacean muscle (Atwood 1973) and because of the vast diversity of muscle types within the animal kingdom (Hoyle 1983), some have suggested that the sliding ¢lament model o¡ers little more than a general qualitative description of the relation between the structural features of muscle and performance ( Jahromi & Atwood 1969;Hoyle 1983).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that crustaceans are able to generate higher maximum muscle stresses than vertebrates and most insects ( Josephson 1993). However, the physiological basis of this di¡erence has remained unresolved: are the higher stresses due simply to increases in the resting sarcomere length or is it necessary to invoke other ¢breassociated traits such as the density of the myosin ¢laments ( Jahromi & Atwood 1969;West et al 1992), arthropod`catch-like' e¡ects (GÏnzel & Rathmayer 1994), the myo¢brillar bundle diameter (Hilber & Galler 1998), di¡erences in the actin^myosin ¢lament ratios ( Jahromi & Atwood 1969;West et al 1992) and potential di¡erences in the actin^myosin cross-bridge duty factors (Cooke 1997)? Because of the heterogeneous nature of crustacean muscle (Atwood 1973) and because of the vast diversity of muscle types within the animal kingdom (Hoyle 1983), some have suggested that the sliding ¢lament model o¡ers little more than a general qualitative description of the relation between the structural features of muscle and performance ( Jahromi & Atwood 1969;Hoyle 1983).…”
Section: Resultsmentioning
confidence: 99%
“…This effect describes the phenomenon that a short, high-frequency discharge of a motoneuron leads to a long-lasting increase in force production of a muscle that is maintained at a low frequency of motoneuron discharge. The effect has been described for crustacean muscles (Blaschko et al, 1931;Günzel and Rathmayer, The Journal of Experimental Biology 216 (6) 1994), locust tibial muscles (Wilson and Larimer, 1968) and the mesothoracic extensor tibiae in the stick insect Carausius morosus (Guschlbauer, 2009). If trochanteral muscles of stick insects possess catch-like properties, such an effect might hold the leg in the region of the PO.…”
Section: Targeted Movements Shift In Average Leg Positionmentioning
confidence: 99%
“…This clearly differs from molluscan catch in that nerve stimulation and actomyosin activation occur throughout the contraction. The mechanism underlying this phenomenon is not well understood, although in one invertebrate case may arise in part from non-uniform sarcomere lengths (Günzel and Rathmayer, 1994).…”
Section: Post-1997-mentioning
confidence: 99%